2013
DOI: 10.1095/biolreprod.112.104802
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Genome-Wide Methylation and Gene Expression Analyses Reveal Signaling Pathways Involved in Ovarian Dysfunction after Developmental EDC Exposure in Rats1

Abstract: Transient exposure to methoxychlor (MXC), an environmental endocrine-disrupting chemical, during fetal and neonatal stages causes ovarian dysfunction in pubertal, adult, and aging animals. Adult animals have reduced number of ovulations and abnormal follicular composition associated with altered gene expression and DNA methylation patterns. To test the hypothesis that the ovarian epigenomic changes induced by MXC are detectable following the exposure period, leading to altered gene expression by adulthood, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 74 publications
1
27
0
Order By: Relevance
“…This finding correlates with the lack of significant effects on the levels of ESR1 protein in the adult ovary [24,160]. Further analysis has shown that the DNA methylation levels in the promoter regions of these genes were unchanged in neonatal ovaries (PND 7) immediately after the exposure [25]. These data demonstrate the age-dependence/hormone responsiveness of the epigenetic changes, which has also been shown in other tissues (e.g., uteri) with other compounds (e.g., DES, genistein) [161].…”
Section: Methoxychlor In Vivo Studiessupporting
confidence: 61%
See 2 more Smart Citations
“…This finding correlates with the lack of significant effects on the levels of ESR1 protein in the adult ovary [24,160]. Further analysis has shown that the DNA methylation levels in the promoter regions of these genes were unchanged in neonatal ovaries (PND 7) immediately after the exposure [25]. These data demonstrate the age-dependence/hormone responsiveness of the epigenetic changes, which has also been shown in other tissues (e.g., uteri) with other compounds (e.g., DES, genistein) [161].…”
Section: Methoxychlor In Vivo Studiessupporting
confidence: 61%
“…A more recent targeted genome-wide methylation array study has revealed that members of essential signaling pathways are hypermethylated and their gene expression down-regulated in MXC-treated ovaries. IGF-1 signaling was the most significantly affected pathway wherein several members of the family -Igf1r, insulin receptor (Insr), Pik3r1, Hras, and Foxo3 -were hypermethylated [25]. These data suggested that the initial DNA methylation patterns were representative of the gene expression patterns responsive to the EDC exposure and not the adult hypermethylation events.…”
Section: Methoxychlor In Vivo Studiesmentioning
confidence: 96%
See 1 more Smart Citation
“…From activated murine follicles, mature oocytes could be retrieved for IVF and embryo transfer, followed by delivery of healthy pups with proven fertility. Recently, Zama & Uzumcu (2013) have demonstrated an age-dependent effect on epigenetic alterations in key molecules of specific signaling pathways such as PTEN, and IGF1, or rapid estrogen signaling on developmental exposure of rats to methoxychlor, an environmental endocrine-disrupting chemical. Hypermethylation of Igf1r, Pi3kr, and Foxo3 had an effect on follicular maturation supported by reduced ovulations observed in treated ovaries.…”
Section: Pi3k/pten/akt and Tsc/mtor Pathwaysmentioning
confidence: 99%
“…In animal models, environmental infl uences on epigenetic mechanisms have been transmitted trans-generationally. A targeted genome-wide methylation study in rats using Nimblegen 3x720K CpG Island Plus RefSeq Promoter Arrays found that key molecules in specifi c pathways, including PTEN, IGF-1, or rapid estrogen signaling were epigenetically altered in methoxychlor-exposed ovaries (Zama and Uzumcu 2013 ). It has also been reported that early life exposures to endocrine disruptors may alter gene expression in hypothalamic nuclei via DNA methylation and histone acetylation (De Coster and van Larebeke 2012 ;Gore 2008 ).…”
Section: Endocrine Disruptorsmentioning
confidence: 99%